Femoral Nerve injury from slip and fall: A novel presentation of debilitating injury - Phillip Karsen; Jeremiah Long; Shelley Noland; Christian McElvaney; Karan Patel (Journal of Orthopaedic Case Reports)
Introduction: Femoral nerve injury is a recognized complication of abdominal, pelvic, and orthopedic surgeries. It can also occur due to pelvic fractures, intra-abdominal trauma, and hip injuries. These injuries often result in pain, weakness, and difficulty with ambulation, significantly impacting a patient’s quality of life. Case Report: We report the case of a 72-year-old male who developed femoral nerve palsy while exiting a hot tub. The unusual mechanism of injury initially led to a missed diagnosis, delaying appropriate treatment. Following an extensive diagnostic workup, femoral nerve palsy was identified as the cause of his disability. Timely intervention ultimately led to the resolution of his symptoms. Conclusion: This case highlights a novel mechanism of femoral nerve palsy and underscores the importance of prompt diagnosis for optimal outcomes. Clinicians must maintain a high index of suspicion for rare injury mechanisms to avoid delays in treatment.